2000
DOI: 10.1103/physrevb.62.7219
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of surface reconstruction to specular RHEED intensity on GaAs(001)

Abstract: By carrying out atomic-scale growth simulations of a GaAs(001)-␤2(2ϫ4) surface, we find that the density of double As dimers evolves synchronously with the observed specular reflection high-energy electrondiffraction ͑RHEED͒ intensities in growth and after its interruption. At the same time, we find that a step density does not even oscillate during growth. We further show that the structural transition of initial growing islands from a non-͑2ϫ4͒ structure to the ␤2(2ϫ4) structure found previously can be detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…The feature at 265 cm −1 and the very weak feature approximately at 277 cm −1 in the experimental spectra (figure 2) can be a result of the presence of large GaAs islands with the average thickness 1 ML and more. The possibility of the presence of GaAs islands with the filled trenches was shown by Itoh and Ohno [15,16]. The calculated Raman spectra of the GaAs layers grown on the (001)-(2 × 4) reconstructed AlAs surface with the thickness from 1 to 1.5 ML are presented in figure 5.…”
Section: Study Of Gaas Islands Formed On a (001)-(2 × 4) Alas Interfacementioning
confidence: 87%
“…The feature at 265 cm −1 and the very weak feature approximately at 277 cm −1 in the experimental spectra (figure 2) can be a result of the presence of large GaAs islands with the average thickness 1 ML and more. The possibility of the presence of GaAs islands with the filled trenches was shown by Itoh and Ohno [15,16]. The calculated Raman spectra of the GaAs layers grown on the (001)-(2 × 4) reconstructed AlAs surface with the thickness from 1 to 1.5 ML are presented in figure 5.…”
Section: Study Of Gaas Islands Formed On a (001)-(2 × 4) Alas Interfacementioning
confidence: 87%
“…In contrast to this, the B1a step edge enjoys its stability when it is straight in the ͓110͔ direction, and it is this difference that causes both sides to grow differently from each other. To confirm this, we carry out the growth simulations by choosing the same growth conditions as before, 8,9,[15][16][17] i.e., f Ga ϭ0.1 ML/s, f As 2 ϭ0.4 ML/s, and Tϭ580°C. By so doing, one can clarify the influence of atomic steps on the growth morphology by comparing the current results with the previous ones.…”
mentioning
confidence: 89%
“…9, 15 We have also reproduced the principal features of the temporal evolution of a specular intensity of RHEED by calculating the density of double As dimers characterizing the ␤2(2ϫ4) structure. 16 Recently, we also reported our results of the kMC simulations on the step-flow growth modes of both the A and B steps, which are parallel to the ͓1 10͔ direction and to the ͓110͔ direction, respectively. 17 By these simulations, it has been found that the kinetics of both species play crucial roles for the growth anisotropy between A and B steps due to the fact that there is a difference in the number of Ga adatoms needed for a terrace edge to accommodate an As dimer so as to enable the growth.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…9 Since the double As dimers characterize the ␤2͑2 ϫ 4͒ reconstruction, our result results from the fact that the time dependent part of a RHEED intensity comprises a minor portion of the total intensity, so that to the first order approximation, the time evolution of a specular RHEED intensity is proportional to the summation of the time evolutions of the relevant surface features. 9 Since the double As dimers characterize the ␤2͑2 ϫ 4͒ reconstruction, our result results from the fact that the time dependent part of a RHEED intensity comprises a minor portion of the total intensity, so that to the first order approximation, the time evolution of a specular RHEED intensity is proportional to the summation of the time evolutions of the relevant surface features.…”
mentioning
confidence: 95%